Dynamics of State and Religion Relations in the Political Paradigm: The Role of Religious Organizations in Contemporary Indonesian Public Policy - Bina Prima Panggayuh; Muhammad Hafiz Rivaldi; Faizatunnisa; Alvira Syahila; Berliana Roisanti (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2026)
This research discusses the dynamics of the relationship between the state and religion within the political paradigm. The problem addressed in this study is how the dynamics of the relationship between the state and religion in Indonesia are manifested in the contemporary political paradigm, and to what extent Religious Organizations (ROs) act as actors influencing and shaping public policy. The purpose of this study is to analyze the dynamics of the relationship between the state and religion within Indonesia's contemporary political paradigm. The main focus of the research is to explore the role of religious organizations in influencing the formation and implementation of public policies. Through a literature review, this study explores how the interaction between Political powers and religious institutions shapes policy directions oriented towards religious values and its impact on state governance. The research findings are expected to provide a deep understanding of the strategic position of religious organizations in the national political context as well as their contribution to the public decision-making process in Indonesia today.